Fundamentals of Phonology: Understanding the Sounds of a Language in Simple Ways - Nur Hapsi Harahap; Yani Lubis; Putri Fadila Ramadhani (Tinta Emas Publisher, 2023)
Phonology is a branch of linguistics that studies the sound system of language. Although it is a complex field, a basic understanding of phonology can help individuals understand and analyze simple language sounds. This abstract aimed to present a brief description of the basics of phonology and the importance of understanding phonological principles in linguistic studies. We explore basic concepts such as phonemes, allophones, and phonological rules in forming the sound system of a language. In this abstract, we also underscore the importance of phonology in language teaching and learning. Phonological understanding can help language learners to recognize and distinguish similar language sounds that have different meanings. Through an emphasis on a simplistic approach, this abstract provides a basic understanding that can be used as a foundation for those interested in studying phonology without having to engage in complex empirical research. This research is based on a comprehensive literature review of the foundations of phonology. This approach does not involve empirical research or the collection of new primary data but gathers information from relevant secondary sources such as textbooks, academic journals, online articles, and other trusted sources.